УСИЛЕНИЕ ЭЛЕКТРИЧЕСКОГО ПОЛЯ В ДИЭЛЕКТРИЧЕСКОМ ПРОМЕЖУТКЕ МЕЖДУ ПРОВОДЯЩИМИ ВКЛЮЧЕНИЯМИ - Щерба, М.А.; Подольцев, А.Д. (Інститут електродинаміки НАН України, Київ, 2011)
The mathematic model for numerical analysis of external low frequency electric field (EF) disturbance in the dielectric gap between two closely located conducting inclusions, which are placed along the field on a distance less than its sizes, is developed. It is shown that at decreasing of gap between surfaces such inclusions the field intensity inside this gap increases according to the law of power function. Also it is revealed that for fixed sizes conducting inclusions, which located in the line of field, the degree of field intensity in a dielectric gap raises at decreasing of distance between them and with increasing its surfaces curvature. The performed calculations corroborated that at approaching of cylindrical, spherical and ellipsoidal inclusions the degree of field intensity between the last-named is largest, and between the first-named is lowest. References 8, figures 5.